Olmedo y Quintana: de la lealtad al rey a la soberanía de la nación como tensión en el discurso lírico independentista - Zevallos, Johnny (2021)
The poetic work of Ecuadorian José Joaquín de Olmedo and Spanish Manuel José Quintana pretend to represent the political and institutional crisis that the Andean area was going through in its transit from viceroyalty to republic as well as the peninsula in its attempt to regain political sovereignty after the Napoleonic invasion. Furthermore, by being participants, in their capacities as deputy and political journalist,respectively, during one of the founding moments in the legal organization of Hispanic American nations: the Cortes de Cádiz, it is necessary to approach their poetic projects from another perspective. In addition, both coincide in proposing scenarios that move from the old regime to the liberal system by introducing seminars that aspire to reproduce, in the first instance, a theologicalpolitical discourse that directed the social andcultural imaginaries for, in a second moment, aim at a broader legal stage: the constitutional discourse and the rupture of the imperial space. Therefore, I am interested in recognizing not only rhetorical-figurative strategies but, above all, the sociopolitical imaginary constructed by the lettered city in the poetic proposals of Olmedo and Quintana, and how these varied according to the irruption of renewal aesthetic-political models, product of Cadiz constitutional pattern, and that will unleash in different independence movementsin Hispanic America.